Predictors of cerebrospinal fluid GeneXpert MTB/RIF positivity in patients with tuberculous meningitis: A prospective cohort study - Priyanka Gupta; Neeraj Kumar; Ravindra Kumar Garg; Hardeep Singh Malhotra; Imran Rizvi; Rajesh Verma; Praveen Kumar Sharma; Ravi Uniyal; Shweta Pandey; Amita Jain; Parul Jain (Asian Pacific Journal of Tropical Medicine)
Objective: To identify the clinical, laboratory, and radiological markers that could predict a positive GeneXpert result in patients suspected of tuberculous meningitis. Methods: In this prospective, observational study, patients with tuberculous meningitis were systematically evaluated. Various clinical, laboratory [including cerebrospinal fluid (CSF) microscopy, culture, and GeneXpert], and neuroimaging factors were examined. All participants were administered anti-tuberculous treatment and corticosteroids. A six-month follow-up was done to evaluate the outcome. Results: Of the 116 patients studied, 54 (46.6%) tested positive for GeneXpert, while 62 (53.4%) were negative. Third cranial nerve involvement (OR 3.71, 95% CI 1.052-13.09, P=0.04) and the presence of basal exudates on neuroimaging (OR 5.22, 95% CI 2.03-13.42, P=0.001) emerged as independent predictive factors for a positive GeneXpert result. A positive CSF GeneXpert result (P=0.002) and drug resistance (P=0.004) were significantly linked to adverse outcomes. Additionally, a high score on the Medical Research Council stage III (OR 5.64, 95% CI 1.18-26.87, P=0.03) and elevated CSF cell counts (OR 1.002, 95% CI 1.00-1.001, P=0.03) were identified as independent predictors of poor prognosis. Conclusions: Third cranial nerve involvement and the presence of basal exudates were significant indicators of a positive GeneXpert result. MRC stage III disability and elevated CSF cell counts predicted poor outcomes.